Comparison of Shiga toxin-encoding bacteriophages in highly pathogenic strains of Shiga toxin-producing Escherichia coli O157:H7 in the UK. Issue 3 (25th February 2020) - Yara, Daniel A.; Greig, David R.; Gally, David L.; Dallman, Timothy J.; Jenkins, Claire
Abstract : Over the last 35 years in the UK, the burden of Shiga toxin-producing Escherichia coli (STEC) O157:H7 infection has, during different periods of time, been associated with five different sub-lineages (1983–1995, Ia, I/IIa and I/IIb; 1996–2014, Ic; and 2015–2018, IIb). The acquisition of a stx2a -encoding bacteriophage by these five sub-lineages appears to have coincided with their respective emergences. The Oxford Nanopore Technologies (ONT) system was used to sequence, characterize and compare the stx -encoding prophages harboured by each sub-lineage to investigate the integration of this key virulence factor. The stx2a -encoding prophages from each of the lineages causing clinical disease in the UK were all different, including the two UK sub-lineages (Ia and I/IIa) circulating concurrently and causing severe disease in the early 1980s. Comparisons between the stx2a- encoding prophage in sub-lineages I/IIb and IIb revealed similarity to the prophage commonly found to encode stx2c, and the same site of bacteriophage integration ( sbcB ) as stx2c -encoding prophage. These data suggest independent acquisition of previously unobserved stx2a -encoding phage is more likely to have contributed to the emergence of STEC O157:H7 sub-lineages in the UK than intra-UK lineage to lineage phage transmission. In contrast, the stx2c -encoding prophage showed a high level of similarity across lineages and time, consistent with the model of stx2c being present in the common ancestor to extant STEC O157:H7 and maintained by vertical inheritance in the majority of the population. Studying the nature of the stx -encoding bacteriophage contributes to our understanding of the emergence of highly pathogenic strains of STEC O157:H7.